2016
DOI: 10.1111/pan.12999
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrasound‐guided transversus abdominis plane (TAP) block on postoperative analgesia and neuroendocrine stress response in pediatric patients undergoing elective open inguinal hernia repair

Abstract: TAP block is effective as a part of multimodal analgesia for children undergoing open inguinal hernia repair with significant attenuation in the neuroendocrine stress response induced by surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
23
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
(30 reference statements)
1
23
2
Order By: Relevance
“…This meta-analysis suggested that TAP block significantly reduced pain intensity during PAR after CRS both at rest and during movement; however, it only reduced pain 24 h after surgery during movement but not at rest. Similar pain relief has been reported for other abdominal surgeries [19,22]. A clinical trial conducted by Røjskjaer et al [22] suggested that TAP block significantly reduced pain intensity 8 h after abdominal hysterectomy.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…This meta-analysis suggested that TAP block significantly reduced pain intensity during PAR after CRS both at rest and during movement; however, it only reduced pain 24 h after surgery during movement but not at rest. Similar pain relief has been reported for other abdominal surgeries [19,22]. A clinical trial conducted by Røjskjaer et al [22] suggested that TAP block significantly reduced pain intensity 8 h after abdominal hysterectomy.…”
Section: Discussionmentioning
confidence: 50%
“…TAP block has been proven to be effective for the reduction of postoperative pain intensity after lower abdominal surgery under the umbilicus, especially within 24 h after surgery [19][20][21]. This meta-analysis suggested that TAP block significantly reduced pain intensity during PAR after CRS both at rest and during movement; however, it only reduced pain 24 h after surgery during movement but not at rest.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In addition, many LA dosing studies that have been performed in children often generated inconclusive results. [6][7][8][9][10] As a result of this large knowledge gap, ESRA and ASRA decided to convene a committee to look at an evidence-based approach to dosing guidelines in children.…”
mentioning
confidence: 99%
“…There have been reports that larger volume of the local anaesthetic (1-2 mL kg -1 ) may spread to the paravertebral space and extend a range of analgesia, providing partial exclusion of the painful stimuli from the viscera [9]. Previous research results mainly show that the TAP block decreases pain perception, reduces the requirement for analgesics in the postoperative period and increases time span from the end of the anaesthesia to the first dose of analgesics in children after abdominal surgery [3,10,11]. However, there are also individual reports which do not confirm this data [12,13].…”
Section: Discussionmentioning
confidence: 99%